Rotary endodontic files versus manual files for root canal treatment - Rajkhan, Wael Hisham; Alasmari, Abdullah Hussain; Alhadi, Abduljalil Bader; Alharbi, Abrar Zainalabiddin; Khwaji, Nwaf Mohammed; Alannaz, Remaz Fahad; Alshehri, Hassan Awadh; Almalaq, Abdulaziz Ali; Alharbi, Wasim Ghazi; Alhindi, Anwar Fawzi; Alanazi, Sarah Hatab (International Journal Of Community Medicine And Public Health, 2021)
Many studies have been published to compare the efficacy of root canal filling with either rotary and manual instrumentation. The most commonly reported factors included instrumentation, obturation time and to obturation quality. Besides, the different studies in the literature have used different assessment tools and parameters of their outcomes. In addition, to using different rotary instrumentation techniques. In thisliterature review, we have formulated strong evidence regarding the effectiveness of rotary and manual instrumentation files for root canal filling based on the findings from the current studies in the literature. Our results indicate the effectiveness of rotary instrumentation in reducing the root canal instrumentation time and enhancing the obturation and filling quality as compared to the manual instrumentation techniques. Our findings also indicate the potential variability in the effectiveness between the different rotary instrumentation techniques. However, it was not an area of concentration among the different studies in the literature. Thus, to formulate such evidence, further relevant investigations to this topic might be required. Finally, we recommend that rotary endodontic files should be indicated for the root canal filling settings to obtain better outcomes and alleviate the associated quality of work.